Genetic Evaluation of Schizophrenia Using the Illumina HumanExome Chip - Moons, Tim (PLoS One, 2016)
INTRODUCTION: Schizophrenia is a genetically heterogeneous disorder that is associated with several common and rare genetic variants. As technology involved, cost advantages of chip based genotyping was combined with information about rare variants, resulting in the Infinium HumanExome Beadchip. Using this chip, a sample of 493 patients with schizophrenia or schizoaffective disorder and 484 healthy controls was genotyped. RESULTS: From the initial 242901 SNVs, 88306 had at least one minor allele and passed quality control. No variant reached genomewide-significant results (p<10(-8)). The SNP with the lowest p-value was rs1230345 in WISP3 (p = 3.05*10(−6)), followed by rs9311525 in CACNA2D3 (p = 1.03*10(−5)) and rs1558557 (p = 3.85*10(−05)) on chromosome 7. At the gene level, 3 genes were of interest: WISP3, on chromosome 6q21, a signally protein from the extracellular matrix. A second candidate gene is CACNA2D3, a regulator of the intracerebral calcium pathway. A third gene is TNFSF10, associated with p53 mediated apoptosis.